(3JHUQI GdbVGI hGdENhGf aj hVY GdHO heG jTgO dg ef GdHQgGfs - (3MSf GdYOhj GdMeRGhj,J (B1303 (3g` s
(3ChdgG (B:s
(3CfLhe RgQ RgQJ aj GdOLfI Ce Sjha dhGeY hCSfg Ce fUhU bhGWY bO CHGfJ Yf eJjf GdeJhf Sgd GdCYfg s
(3BNQgG (B:s
(3hgPG UQjM daXg QMeg Gddg hfaYfG Hg hgPG BNQ eG jSQ Gddg ddYHO GdSbje cdeG PcQc GdPGcQhf hZad Yf PcQg GdZGadhf s
(3GdfSNI HgG MhGTs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B199 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B3 - (3U (B244s
(3EjVGM Gdecfhf ddHZOGOi(B: (3L (B1 - (3U (B222s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG EWGQGJ s
Keywords: (3Gdabg GdeGdcjs